2014
DOI: 10.1111/cmi.12337
|View full text |Cite
|
Sign up to set email alerts
|

Identification and characterization ofToxoplasma SIP, a conserved apicomplexan cytoskeleton protein involved in maintaining the shape, motility and virulence of the parasite

Abstract: Summary Apicomplexa possess a complex pellicle that is composed of a plasma membrane and a closely apposed inner membrane complex (IMC) that serves as a support for the actin-myosin motor required for motility and host cell invasion. The IMC consists of longitudinal plates of flattened vesicles, fused together and lined on the cytoplasmic side by a subpellicular network of intermediate filament-like proteins. The spatial organization of the IMC has been well described by electron microscopy, but its compositio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
36
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 47 publications
1
36
0
Order By: Relevance
“…Their localization at the transverse but not the longitudinal sutures was confirmed by co‐staining with ISC1 (Figure c). This staining pattern is similar to a previously identified protein in the transverse sutures called CBAP/SIP (Lentini et al ., ; Tilley, Krishnamurthy, Westwood, & Ward, ), which also ranked highly in the ISC4‐BioID data set (Figure e). Based on their localization, we named this new class of proteins as TSCs (CBAP/SIP was designated as TSC1).…”
Section: Resultsmentioning
confidence: 87%
See 1 more Smart Citation
“…Their localization at the transverse but not the longitudinal sutures was confirmed by co‐staining with ISC1 (Figure c). This staining pattern is similar to a previously identified protein in the transverse sutures called CBAP/SIP (Lentini et al ., ; Tilley, Krishnamurthy, Westwood, & Ward, ), which also ranked highly in the ISC4‐BioID data set (Figure e). Based on their localization, we named this new class of proteins as TSCs (CBAP/SIP was designated as TSC1).…”
Section: Resultsmentioning
confidence: 87%
“…To determine if ISC3 plays a role in parasite morphology, we examined extracellular ISC3 knockouts using light microscopy, as a similar function has been described for CBAP/SIP/TSC1 (Lentini et al ., ; Tilley et al , ). We found that disruption of ISC3 results in shorter and wider parasites, giving these knockouts a bloated appearance compared with the parental strain (Figure a).…”
Section: Resultsmentioning
confidence: 98%
“…A). Recently, it has been reported that morphological modifications affect the ability of mutant parasites to invade host cells (Lentini et al ., ). Interestingly, invasion assays allowed us to establish that the level of invasion by TgArk3‐depleted parasites was reduced to 44% of that showed by control parasites grown in the presence of ATc (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Intracellular tachyzoites treated with low levels of the dinitroaniline oryzalin can assemble short microtubules that are sufficient to complete nuclear division and budding; these parasites have shortened subpellicular microtubules and are noninvasive, likely because they fail to adequately immobilize MyoA to power host cell entry (9). Other cytoskeletal proteins that influence shape also alter move-ment: tachyzoites lacking the IMC proteins PHIL1, SIP, and CBAP are shorter and wider than wild-type parasites and have reduced motility (128,130,131). Conoid extrusion is specifically inhibited by a small molecule, conoidin A, which was identified in a screen for invasion inhibitors (132,133).…”
Section: Microtubule-dependent Processesmentioning
confidence: 99%